2017
DOI: 10.1186/s12864-017-3694-6
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-enriched proteome changes and prion protein expression during neural differentiation and in neuroblastoma cells

Abstract: BackgroundThe function of the prion protein, involved in the so-called prion diseases, remains a subject of intense debate and the possibility that it works as a pleiotropic protein through the interaction with multiple membrane proteins is somehow supported by recent reports. Therefore, the use of proteomic and bioinformatics combined to uncover cellular processes occurring together with changes in the expression of the prion protein may provide further insight into the putative pleiotropic role of the prion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…We performed a meta-analysis on published genomic and proteomic data to confirm the validity of our model and to exclude that the knock-down of PrP C might in some way interfere with the expression of other tau receptors (Morozova et al, 2019;Rauch et al, 2018). Concerning N2a cell line, we found that specific tau re- with a specific focus on membrane proteins (Macedo et al, 2017).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We performed a meta-analysis on published genomic and proteomic data to confirm the validity of our model and to exclude that the knock-down of PrP C might in some way interfere with the expression of other tau receptors (Morozova et al, 2019;Rauch et al, 2018). Concerning N2a cell line, we found that specific tau re- with a specific focus on membrane proteins (Macedo et al, 2017).…”
Section: Discussionmentioning
confidence: 84%
“…More recently, Macedo et al . conducted a proteomic study on wild‐type and Prnp ‐/‐ PK1 neuroblastoma cell line to identify all differentially expressed proteins, with a specific focus on membrane proteins (Macedo et al., 2017). The analysis resulted in six differentially expressed proteins, none of which has ever been associated to the process of tau internalization.…”
Section: Discussionmentioning
confidence: 99%